PERGESERAN KOMPOSISI GULMA PADA TANAMAN PAPAYA (Carica papaya) YANG DIBERI PUPUK ORGANIK DAN ANORGANIK - Yernelis Syawal (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2010)
ABSTRACT This study aims to see a shift in the composition of the weed on papaya plants fed organic fertilizer (pukana) and inorganic (NPK). And analyze its effect on dry weight of weeds. Research done at the Garden Village folk Sukasari Kec. Talang Kelapa, Palembang, South Sumatra, from June to October 2010. Randomized studies using Design Group (RAK) with 5 treatments and 5 replications. Fertilizer treatments consisted of: P1 = 30 kg plant pukana -1, P2 = 100 g NPK tanaman-1, P3 = 30 kg + 100 g of NPK plant pukana -1, P4 = 25 kg + 200 g of NPK plant pukana-1, P5 = 20 kg + 300 g of NPK plant pukana -1. To determine the dominant weeds were analyzed by the method of squares. The results showed that a shift in the composition of the weeds before cultivation and after treatment fertilizer age 1 month, 2 months and 3 months. Before tilling the land is dominated by Imperata cylindrica, Cyperus rotundus and, Mimosa invisa, while after treatment is dominated by the weed Ageratum conyzoides and Echinochloa colonum both at age 1, 2 and 3 months after planting. The results of the diversity of the highest weed dry weight obtained in the treatment of P3 is 81.85 g and the lowest in the treatment of P2 with weight 37.85 g.Keywords: Shifts, Weeds, Papaya, Pukana, NPK